Effect of bio- fertilizers Application and Nutrient Solution Technocal amino calcium boron Sprayon Jujube Transplants growth - Al-Hayani, Ali Mohammed; Lefta, Thakha‘a Majid; Mutlaq , Khamis Habib (Journal of agricultural, environmental and veterinary sciences, 2018)
An experiment was conducted in The research station Horticulture and landscape gardening Dept./college of Agriculture university of Diyala for the period from 24/2/2016 up to 1/6/2017 on Jujube(Ziziphus jujube Mill.) cv. Pear transplants budded on seedling rootstocks in order to reveal the effect of Bio fertilizers application and foliar spray with nutrient solution (Technocal Amino Calcium Boron)on some vegetative characteristics and leaves mineral content. Bio fertilizer application (B) and nutrient solution spray (T) factors were used. The first factor include three levels ,control (B0),The application of combined mixed bacteria (Azospirillum brasilence +Pseudomonas flouresence) at 20 g. plant- 1 (B1), and 40 g. per plant (B2). Nutrient solution (Technocal Amino Calcium Boron) was used in three concentrations, spray with water only (T0),10 ml. L- 1 (T1), and 20 ml. L- 1 , (T2)in factorial experiment Treatments distributed according to Randomized complete Block Design (RCBD)with three replication and Three transplants per experimental unit. Results were as follows: Bio fertilizers combination application (Azospirillum sp. +Pseudomonas sp.) at 40per plant(B2) have a significant superi in most vegetative traits characteristics(plant high ,circumference increase ,chlorophyll relative) whereas This superiority did not reached signifying level over (B1)treatment in leaves chlorophyll relative content for both growth seasons. The same were observed for nutrient solution treatments in increasing vegetative growth parameters, T1 treatment gave the highest significant values for both growth seasons. Biofertilizer application at the two highest levels cgused asignificant increase in all the chemical growth traits which include leaves Nitrogen ,phosphorus , and carbohydrates content during both seasons compared with untreated control. The third level (B2)gave the highest values for the previous elements and carbohydrates compared with the least values achieved in untreated treatment (B0)the same for nutrition solutions where T1 and T2 levels cause a significant increase in chemical traits during both seasons compared with untreated control. The second level (T1) gave the best values for leaves Nitrogen ,phosphorus and carbohydrates During both season.
Keywords: Sidr; bio-fertilizer; vegetative growth; foliar nutrition